Cryptolepine inhibits hepatocellular carcinoma growth through inhibiting interleukin-6/STAT3 signalling - Seth A. Domfeh; Patrick W. Narkwa; Osbourne Quaye; Kwadwo A. Kusi; Gordon A. Awandare; Charles Ansah; Alimatu Salam; Mohamed Mutocheluh (BMC, 2021)
Abstract Background Diverse signalling pathways are involved in carcinogenesis and one of such pathways implicated in many cancers is the interleukin 6/signal transducer and activator of transcription 3 (IL-6/STAT3) signalling pathway. Therefore, inhibition of this pathway is targeted as an anti-cancer intervention. This study aimed to establish the effect of cryptolepine, which is the main bioactive alkaloid in the medicinal plant Cryptolepis sanguinolenta, on the IL-6/STAT3 signalling pathway. Methods First, the effect of cryptolepine on the IL-6/STAT3 pathway in human hepatoma cells (HepG2 cells) was screened using the Cignal Finder Multi-Pathway Reporter Array. Next, to confirm the effect of cryptolepine on the IL-6/STAT3 signalling pathway, the pathway was activated using 200 ng/mL IL-6 in the presence of 0.5-2 μM cryptolepine. The levels of total STAT3, p-STAT3 and IL-23 were assessed by ELISA. Results Cryptolepine downregulated 12 signalling pathways including the IL-6/STAT3 signalling pathway and upregulated 17 signalling pathways. Cryptolepine, in the presence of IL-6, decreased the levels of p-STAT3 and IL-23 in a dose-dependent fashion. Conclusion Our results demonstrated that cryptolepine inhibits the IL-6/STAT3 signalling pathway, and therefore cryptolepine-based remedies such as Cryptolepis sanguinolenta could potentially be used as an effective immunotherapeutic agent for hepatocellular carcinoma and other cancers.